Socialization of Room Division Management in Enhancing the Career Readiness of SMKN 10 Batam Students within the Tourism Sector in the Digital Era - Supardi; Arina Luthfini Lubis; Andri Wibowo; Yudha Wardhani; Zahara Fatimah; Fidya Farasalsabila; Bintang Cendekia (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
This Community Service (PKM) initiative aims to enhance student career readiness through the socialization and fundamental training of hospitality management at SMK Negeri 10 Batam. The program is localized in response to the limited student understanding of sectoral career prospects and deficient digital literacy regarding the use of social media for career exploration. Conducted in March 2026 with 120 participants across grades X, XI, and XII, the methodology employed a holistic, interactive, and applied approach, comprising material dissemination, digital practice, open discussions, and pre-test/post-test evaluations. The results indicate a significant improvement in students' comprehension of hospitality management, with an average increase exceeding 60%. Furthermore, this initiative fostered career motivation and awareness in the digital era and established a framework for sustainable collaboration between academia and educational institutions to align graduates' competencies with the demands of the Business and Industrial World (DUDI).